Hormone replacement therapy improves contractile function and myonuclear organization of single muscle fibres from postmenopausal monozygotic female twin pairs. (30th April 2013) - Qaisar, Rizwan; Renaud, Guillaume; Hedstrom, Yvette; Pöllänen, Eija; Ronkainen, Paula; Kaprio, Jaakko; Alen, Markku; Sipilä, Sarianna; Artemenko, Konstantin; Bergquist, Jonas; Kovanen, Vuokko; Larsson, Lars
Key points: The ageing‐related impairment of muscle function and consequent falls and fall‐related injuries have severe negative effects on morbidity and mortality in old age, with women being more negatively affected than men. The effects of hormone replacement therapy (HRT) on regulation of muscle contraction and myonuclear organization were investigated in monozygous postmenopausal twin pairs where only one twin was an HRT‐user. HRT treatment improved single fibre force‐generating capacity (specific force), without affecting fibre size and speed of contraction, due to fibre type‐specific effects on force and number of force‐generating cross‐bridges. HRT had a significant effect on the myonuclear organization in slow‐twitch muscle fibres, improving the synthetic capacity of the myonuclei and optimizing transport of proteins. Significant positive effects on regulation of muscle contraction and myonuclear organization were observed at the cellular level in response to HRT with consequences for quality of life in postmenopausal women. Abstract Ageing is associated with a decline in muscle mass and strength leading to increased physical dependency in old age. Postmenopausal women experience a greater decline than men of similar age in parallel with the decrease in female sex steroid hormone production. We recruited six monozygous female twin pairs (55–59 years old) where only one twin pair was on hormone replacement therapy (HRT use = 7.8 ± 4.3 years) to investigate the association of HRT with the cytoplasmic volume supported by individual myonuclei (myonuclear domain (MND) size, ) together with specific force at the single fibre level. HRT use was associated with a significantly smaller (∼27%; P < 0.05) mean MND size in muscle fibres expressing the type I but not the IIa myosin heavy chain (MyHC) isoform. In comparison to non‐users, higher specific force was recorded in HRT users both in muscle fibres expressing type I (∼27%; P < 0.05) and type IIa (∼23%; P < 0.05) MyHC isoforms. These differences were fibre‐type dependent, i.e. the higher specific force in fast‐twitch muscle fibres was primarily caused by higher force per cross‐bridge while slow‐twitch fibres relied on both a higher number and force per cross‐bridge. HRT use had no effect on fibre cross‐sectional area (CSA), velocity of unloaded shortening ( V 0 ) and relative proportion of MyHC isoforms. In conclusion, HRT appears to have significant positive effects on both regulation of muscle contraction and myonuclei organization in postmenopausal women.